A Comparative Experimental Investigation of MPPT Controls for Variable Speed Wind Turbines - Dahbi, Abdeldjalil; Benlahbib, Boualam; Benmedjahed, Miloud; Khelfaoui, Abderrahmane; Bouraiou, Ahmed; Aoun, Nouar; Mekhilefd, Saad; Reama, Abdellatif (International Journal of Electrical and Computer Engineering Systems, 2023)
This work presents an experimental comparative investigation between Maximum power point tracking control methods used in variable speed wind turbines. In order to enhance the efficiency of the wind turbine system, the maximum power point tracking control has been applied for extracting and exploiting the maximum available wind power. Furthermore, two maximum power point tracking controls have been analyzed, developed, and investigated in real-time using Dspace. The first was optimal torque control without speed control, whereas the second was with speed control. The maximum power point tracking control performance comparison has been performed in a real-time experimental validation to illustrate the advantages of these control on the real wind energy system. The results have been achieved and discussed, where the power efficiency improvements appeared in the transit time and in the steady-state as well. In addition, the proposed optimal torque control for maximum power point tracking with speed control decreased the response time and oscillations, while it increased the power to an interval of 12,5% to 75% compared to that of strategy without speed control in the steady-state and transit state, respectively.